Regulation of programmed death ligand 1 (PD‐L1) expression by TNF‐related apoptosis‐inducing ligand (TRAIL) in triple‐negative breast cancer cells. Issue 2 (14th October 2022) - Pimentel, Julio M.; Zhou, Jun‐Ying; Wu, Gen Sheng
Abstract: Triple‐negative breast cancer (TNBC) is an aggressive form of breast cancer that lacks targeted therapies. Previous studies have shown that TNBC cells are highly sensitive to tumor necrosis factor (TNF)‐related apoptosis‐inducing ligand (TRAIL), making it a promising agent for treating TNBC. However, the development of TRAIL resistance limits its further clinical development, and the underlying mechanisms are not fully understood. In this study, we report the role of PD‐L1 in TRAIL resistance. Specifically, we found that TRAIL treatment increases PD‐L1 expression in TRAIL‐sensitive cells and that basal PD‐L1 expression is increased in acquired TRAIL‐resistant cells. Mechanistically, we found that increased PD‐L1 expression was accompanied by increased extracellular signal‐regulated kinase (ERK) activation. Using both genetic and pharmacological approaches, we showed that knockdown of ERK by siRNA or inhibition of ERK activation by the mitogen‐activated protein kinase kinase inhibitor U0126 decreased PD‐L1 expression and increased TRAIL‐induced cell death. Furthermore, we found that knockout or knockdown of PD‐L1 enhances TRAIL‐induced apoptosis, suggesting that PD‐L1‐mediated TRAIL resistance is independent of its ability to evade immune suppression. Therefore, this study identifies a noncanonical mechanism by which PD‐L1 promotes TRAIL resistance, which can be potentially exploited for immune checkpoint therapy.